When Profit Outweighs Sustainability: Empirical Evidence from ESG and Firm Value in Indonesia Energy Industry - Sirait, Dita Eka Pertiwi; Mardhiyah, Ainul; Oktavia, Shintami (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to examine the role of sustainability and profitability in influencing firm value within Indonesia’s energy sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Sustainability performance is measured using the Environmental, Social, and Governance (ESG) disclosure score, while profitability is represented by the Return on Assets (ROA). Firm value is proxied by Tobin’s Q ratio. The research sample consists of 32 energy companies selected using a purposive sampling method. Data analysis is conducted using panel data regression with the Fixed Effect Model (FEM) and the Generalized Least Squares (GLS) approach with cross-section weighting to address potential heteroskedasticity issues. The results reveal that ESG disclosure has no significant effect on firm value, whereas profitability exerts a positive and significant influence. Simultaneously, ESG and profitability jointly have a significant impact on firm value. These findings indicate that investors in Indonesia’s energy sector remain more focused on profitability as the primary determinant of firm value, while sustainability performance has yet to become a key consideration in investment decisions. This study contributes to the ongoing discussion on the integration of ESG factors into firm valuation, particularly within emerging market contexts such as Indonesia.